Strengthening resilience and patient safety in healthcare institutions during the COVID-19 pandemic: Experience from a quasi-medical center - Szu-Ying Chen; Shih-Hao Wang; Yi-Ming Wang; Yu-Wei Huang; Shu-Ching Chi (Journal of the Formosan Medical Association)
The COVID-19 global pandemic exposed healthcare system vulnerabilities, further endangering patient safety. This article explores perspectives on resilience and patient safety among healthcare workers using data from the Taiwan Patient Safety Culture Survey (TPSCS) and implementing Patient Safety Leadership Walkrounds (PSLWs) at E-Da Hospital. In 2021 and 2022, 1340 and 1114 staff members from clinical departments completed TPSCS questionnaires, respectively. 89 leaders from clinical departments participated in PSLWs in 2022. Among the four job categories, scores of Safety Attitude Questionnaire (SAQ) were lower among nurses and medical technicians, while perceptions of resilience and work-life balance were lowest among nurses. Between the two-year surveys, nurses exhibited significant decreases in SAQ in 2022 compared to 2021, while perceptions of work condition and work-life balance significantly declined among pharmacists. Resilience perception significantly decreased among all job categories except physicians during the pandemic. Mediation analyses showed teamwork climate, job satisfaction, management, work condition, and work-life balance were directly associated with safety climate, while resilience acts as a mediator, indirectly potentiating these relationships. Through PSLWs, we identified concerns about patient safety, including workforce, systems, processes, equipment, and work environment. Among these, workforce shortages and unsatisfactory pay emerged as the most pressing challenges. Strong leadership was recognized as a crucial factor in enhancing resilience and patient safety. This study suggests that TPSCS and PSLWs are worth regularly promoting among hospital institutions. Additionally, our findings highlight the urgency of healthcare organizations and governmental agencies to undertake policy reforms to improve healthcare workers’ well-being.